Are labor inspections protecting workers' rights? Adding the evidence from size-based labor regulations and fines in Peru - Mariana Viollaz (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2016)
This paper analyzes how changes in the enforcement of labor regulations impact on the compliance rate in a context where the labor rules and the characteristics of the labor inspection system differ by firm size. In addition to the channels analyzed in the existing literature - the deterrence effect of labor inspections and the movement of displaced workers into the informal sector, this paper adds a margin of adjustment not analyzed before: firms can reduce their size to take advantage of lower penalties for violating the labor rules and/or less stringent regulations. I analyze empirically which forces have dominated for workers employed in firms of different size in Peru during 2008-2013. I measure the enforcement of labor regulations as the number of labor inspections per hundred workers at the regional level, and I instrument it using a measure of the arrival cost of labor inspectors to the firms. The findings reveal that the degree of enforcement had little impact on the compliance with labor regulations. The effect of firms reducing their size to enjoy lower fines and/or less stringent regulations was small in magnitude and the direction of the effect was not clear. The general lack of effect of the enforcement measure on the compliance with the labor rules indicates that the labor inspection system is not effective in Peru, either because it is not able to generate the incentives to comply with labor regulations (e.g. because of lack of resources) or because it fails to overcome the consequences of the adjustment process associated to an increase in the compliance level (e.g. displaced workers moving into the informal sector of the economy).
Keywords: 330